Phyla nodiflora modulates apoptosis and cell cycle arrest in breast cancer cell lines, MCF-7 - Liau, Monica (2016)
Phyla nodiflora belongs to Verbenaceae family. It has been widely used as medicinal remedies in curing various types of diseases as it contains several of constituents. However, the precise cytotoxicity of Phyla nodiflora in relation to the apoptosis and cell cycle in breast cancer cell line, MCF-7 remains unclear. In this study, the ability of Phyla nodiflora to act as anticancer agents by modulating apoptotic pathways and cell cycle arrest was studied. Three of the extracts which consists of EA leaf, EA stem and Met stem shows inhibition of MCF-7 with IC₅₀ of 44.02±0.42 µg/ml, 57.27±0.11µg/ml and 96.26±0.43 µg/ml respectively. While for MDA-MB-231 cells, only cells treated with EA stem (79.36±O.58 µg/ml) and Met stem (93.48±0.91 µg/ml) showed IC₅₀ value but not in EA leaf. However, there was no or less inhibition of MCF-10A was observed after treatments. To further understand Phyla nodiflora extracts in modulating apoptosis, MCF-7 was used. Apoptotic morphological changes were also seen in both methylene blue and DAPI staining in treated cells. JC-1 analysis shows that EA leaf extract (47.81±4.06%) has more cells undergone apoptosis through disruption of mitochondrial membrane potential followed by EA stem extracts (31.31±2.59%) and Met stem extracts (13.64±1.80%). In AnnexinV/PI analysis, more cells were undergoing late apoptosis after treated with Met stem (39.09±3.87%) followed by EA leaf (33.93±4.78%) and EA stem extracts (21.35±4.08%). Concurrent with this, cells treated with three different extracts showed different expression of BcI-2, Bax, caspase 8 and caspase 9 proteins. Total 12 related apoptotic genes such as AIFM1, BAD, BCL-2, BIK, BIRCS, BM; DFFA, CASPl4, CASP2, CASPB, CASP9 and TP53 were selected for analysis and different fold change was seen in each of these gene expressions after treated with different type of extracts. Taken together, these results demonstrated that Phyla nodiflora induces the apoptosis pathway with different magnitude. To investigate the effect of plant extracts on cell cycle progression, cells were subjected to PI staining. For all treatments, S phase arrest was observed in MCF-7 cells. Altered expression of cell cycle regulatory proteins such as CDK6, CDK2, cyclin E1 and cyclin A2 suggested the perturbation of cell cycle regulation. In conclusion, these findings suggest that Phyla nodiflora has potential to be developed into anticancer agent(s).